2005
DOI: 10.1258/0049475054620770
|View full text |Cite
|
Sign up to set email alerts
|

Medical interns knowledge of TB in Pakistan

Abstract: Of 460 interns from five Pakistani teaching hospitals surveyed, only 22% correctly identified the estimated number of new TB cases in Pakistan. The majority (96%) knew that droplet infection was the usual mode of transmission. Only 38% considered sputum smears for acid-fast bacilli as the best test for diagnosis of pulmonary TB and 43.5% for follow-up during TB treatment. The recommended four-drug anti-TB regimen was prescribed by 56.5% in the initiation phase and the recommended two-drug combination in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
6
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 3 publications
5
25
6
1
Order By: Relevance
“…[1] In the present study, the most worrisome finding was the lack of knowledge about TB transmission, as only two-third of the interns correctly answered TB transmission. However interns in India (Bangalore), [11] Nigeria, [13] Pakistan [14] and Iran [15] were somewhat better informed, with 98.7%, 88.1%, 96% and 85% respectively knew that droplet infection was the usual mode of transmission compared with 65.2% in our study. A study among interns in Delhi [10] showed poor knowledge about the mode of transmission, with only 4.2% correctly identified TB as a droplet infection.…”
Section: Discussioncontrasting
confidence: 49%
“…[1] In the present study, the most worrisome finding was the lack of knowledge about TB transmission, as only two-third of the interns correctly answered TB transmission. However interns in India (Bangalore), [11] Nigeria, [13] Pakistan [14] and Iran [15] were somewhat better informed, with 98.7%, 88.1%, 96% and 85% respectively knew that droplet infection was the usual mode of transmission compared with 65.2% in our study. A study among interns in Delhi [10] showed poor knowledge about the mode of transmission, with only 4.2% correctly identified TB as a droplet infection.…”
Section: Discussioncontrasting
confidence: 49%
“…In a study from Pakistan, poor recognition of the burden of tuberculosis and its public health significance was equally identified among medical interns in that country. [12] Adequate knowledge regarding diagnosis and a proper prescription written by a practicing physician is as important as treatment compliance by the patient, which has been shown to reduce the emergence of drug-resistant tuberculosis. A number of studies have highlighted the gaps in the knowledge and practice of physicians treating patients with tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…[8,9] Since the inception of Directly Observed Treatment Short Course (DOTS), the awareness, diagnosis, and treatment of tuberculosis have improved considerably. Some studies have documented inadequate tuberculosis knowledge and poor compliance with tuberculosis treatment guidelines among practicing physicians, [10][11][12][13] Such studies need to be conducted regularly to check the compliance about Revised National Tuberculosis Control Programme (RNTCP) and the need for modifying the tuberculosis control program. The objective of the study was to assess and document the knowledge of tuberculosis and its management practices and their adherence among medical interns and post graduate students of all specialities, except tuberculosis and respiratory medicine since their inclusion will lead to bias of the results.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been reported among medical interns in other countries who showed poor knowledge of DOTS prior to appropriate training. 15,16 At the end of the training, there was significant increase in all aspects of DOTS-related knowledge in the intervention group much of which was still retained three months after the training. These findings suggest that once appropriately trained, health workers are likely to comply to the principles of DOTS in TB management, as has been suggested by others.…”
Section: Discussionmentioning
confidence: 94%